Potential Gains from Capital Flight Repatriation for Sub-Saharan African Countries - Fofack, Hippolyte; Ndikumana, Leonce (2012)
Despite the recent increase in capital flows to Sub-Saharan Africa, the region remains largely marginalized in financial globalization and chronically dependent on official development aid. And with the potential decline in the level of official development assistance in a context of global financial crisis, the need to increase domestic resources mobilization as well as non-debt generating external resources is critical now more than ever before. However, the debate on resource mobilization has overlooked an important untapped source of funds consisting of the massive stocks of private wealth stashed in Western financial centers, a substantial part of which left the region in the form of capital flight. This paper argues that the repatriation of flight capital should take a more prominent place in this debate from a moral standpoint and for clear economic reasons. On the moral side, the argument is that a large proportion of the capital flight legitimately belongs to the Africans and therefore must be restituted to the legitimate claimants. The economic argument is that repatriation of flight capital will propel the sub-continent on a higher sustainable growth path while preserving its financial stability and without mortgaging the welfare of its future generations through external borrowing. The analysis in the paper demonstrates quantitatively that the gains from repatriation are large and dominate the expected benefits from other sources such as debt relief. It is estimated that if only a quarter of the stock of capital flight was repatriated to Sub-Saharan Africa, the region would go from trailing to leading other developing regions in terms of domestic investment, thus initiating a big-push -led sustainable long-term economic growth. The paper proposes some strategies for inducing capital flight repatriation, but cautions that the success of this program is contingent on strong political will on the part of African and Western governments and effective coordination and cooperation at the global level.